2002
DOI: 10.2135/cropsci2002.0037
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interactions, Stability, and Agronomic Performance of Soybean with Altered Fatty Acid Profiles

Abstract: traits. Comparisons between reduced (≈40 g kg Ϫ1 ) and normal (≈110 g kg Ϫ1 ) palmitic acid families showed a There has been a major effort to produce soybean [Glycine max significant decrease in seed yield (Rebetzke et al., 1998; (L.) Merr.] lines with modified fatty acid profiles in order to improve quality and develop new uses for soybean oil. Utilization of the lines Ndzana et al., 1994) and total oil content (Ndzana et depends on their agronomic traits and stability of the fatty acid pro-al., 1994) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 2 publications
10
68
0
Order By: Relevance
“…Earlier, we identified several loci controlling SSC in soybean (Dhungana et al 2017) and observed that majority of the QTL for SSC were found to be significantly influenced by the growing environment. Such effects have been observed for other complex traits like forage quality (Asekova et al 2016), isoflavone content (Primomo et al 2005), seed weight , seed protein (Panthee et al 2005), fatty acid composition, oil and protein contents (Rennie and Tanner 1989;Dornbos and Mullen 1992;Primomo et al 2002;Fehr et al 2003;Hou et al 2006;Oliva et al 2006;Dhakal et al 2013;Asekova et al 2014), and yield (Rao et al 2002;Shen et al 2006) in soybean.…”
Section: Introductionmentioning
confidence: 93%
“…Earlier, we identified several loci controlling SSC in soybean (Dhungana et al 2017) and observed that majority of the QTL for SSC were found to be significantly influenced by the growing environment. Such effects have been observed for other complex traits like forage quality (Asekova et al 2016), isoflavone content (Primomo et al 2005), seed weight , seed protein (Panthee et al 2005), fatty acid composition, oil and protein contents (Rennie and Tanner 1989;Dornbos and Mullen 1992;Primomo et al 2002;Fehr et al 2003;Hou et al 2006;Oliva et al 2006;Dhakal et al 2013;Asekova et al 2014), and yield (Rao et al 2002;Shen et al 2006) in soybean.…”
Section: Introductionmentioning
confidence: 93%
“…AG3906 and TN07-93RR in Knoxville, TN contained greater than 17 wt% saturated FAME, whereas AG3906 and TN07-93RR from the other two locations contained less than 16.5 wt% of these constituents. Studies conducted by Primomo et al [29] showed different factors affect different fatty acid profiles. Palmitic acid, a saturated fatty acid, were shown to be the most stable fatty acid in soybeans.…”
Section: Fuel Propertiesmentioning
confidence: 99%
“…Many studies have shown that temperature fluctuations, seasonal variations, and different geographical locations might influence the fatty acid composition in soybean plants Primomo et al 2002;Bachlava et al 2008;La et al 2014). The yield of Hosim was observed to be stable across locations, and was not affected by increases in oleic acid concentrations.…”
Section: Discussionmentioning
confidence: 96%